Infliximab induction regimens in steroid‐refractory acute severe colitis: a multicentre retrospective cohort study with propensity score analysis. Issue 6 (27th August 2019) - Sebastian, Shaji; Myers, Sally; Argyriou, Konstantinos; Martin, Gayle; Los, Louis; Fiske, Joseph; Ranjan, Ravi; Cooper, Benjamin; Goodoory, Vivek; Ching, Hey‐Long; Jayasooriya, NishaniLalanthika; Brooks, Johanne; et al.
Summary: Background: Accelerated induction regimens of infliximab have been proposed to improve response rates in patients with steroid‐refractory acute severe colitis. Aim: To determine the differences in outcome for acute severe ulcerative colitis between accelerated and standard‐dose infliximab Methods: We collected data on hospitalised patients receiving differing regimens of rescue therapy for steroid‐refractory acute severe ulcerative colitis. Our primary outcome was 30‐day colectomy rate. Secondary outcomes were colectomy within index admission, and at 90 days and 12 months. We used propensity score analysis with optimal calliper matching using high risk covariates defined a priori to reduce potential provider selection bias. Results: We included 131 patients receiving infliximab rescue therapy; 102 received standard induction and 29 received accelerated induction. In the unmatched cohort, there was no difference by type of induction in the 30‐day colectomy rates (18% vs 20%, P = .45), colectomy during index admission (13% vs 20%, P = .26) or overall colectomy (20% vs 24%, P = .38). In the propensity score‐matched cohort of 52 patients, 30‐day colectomy (57% vs 27%, P = .048) and index admission colectomy (53% vs 23%, P = .045) rates were higher in those receiving standard induction compared to accelerated induction but there was no difference in overall colectomy rates (57% vs 31%, P = .09). There was no significant difference in length of stay or in complication and infection rates. Conclusion: In a propensity score‐matched cohort, steroid‐refractory acute severe ulcerative colitis patients, short‐term, but not long‐term, colectomy rates appear to be lower in those receiving an accelerated induction regimen. Abstract : LINKED CONTENT This article is linked to Laharie and Rivière and Sebastian papers. To view these articles, visit https://doi.org/10.1111/apt.15520 and https://doi.org/10.1111/apt.15569 .